2020
DOI: 10.1111/jocn.15418
|View full text |Cite
|
Sign up to set email alerts
|

The impact of inflammatory bowel disease on sexual health in men: A scoping review

Abstract: Aims and objectives To review the literature on the impact of inflammatory bowel disease on the sexual health of men and make recommendations for nursing practice and research. Background Inflammatory bowel disease is a chronic condition of the gastrointestinal tract, causing symptoms that may impact upon sexual health. Specialist nurses are well positioned to assess and manage sexual health, but there is a lack of clinical guidance, especially in relation to men. Design A systematic scoping review following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Of the 50 studies that fulfilled the inclusion criteria, only two studies give explicit attention to the nursing profession (Cockle‐Hearne et al, 2013; Ma et al, 2020). In total, 19 studies emphasize the profession of nursing in their results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 50 studies that fulfilled the inclusion criteria, only two studies give explicit attention to the nursing profession (Cockle‐Hearne et al, 2013; Ma et al, 2020). In total, 19 studies emphasize the profession of nursing in their results.…”
Section: Resultsmentioning
confidence: 99%
“…F I G U R E 1 PRISMA flowchart for study selection. Adopted from PRISMA statement (Page et al, 2021) To explore the patient's perception of the impact of severe asthma on intimacy, establish their information needs and their perceived role of the HCP Albers et al, 2020;Cooper et al, 2018;Dellenborg et al, 2020;Egerod et al, 2018;Fourie et al, 2021;Holmes et al, 2019;Hyde et al, 2020;Josefsson & Gard, 2012;Kazmerski et al, 2016;Leonardi-Warren et al, 2016;Lindau et al, 2011;Ma et al, 2020;den Ouden et al, 2019;Petit-Steeghs et al, 2020;Savel et al, 2020;Traa et al, 2014;Traumer et al, 2019;Zhang et al, 2020 Being asked questions Hoorsan et al, 2021;Sandfort et al, 2013;Traumer et al, 2019 Bringing up the issue themselves Grondhuis Palacios et al, 2018;Hoorsan et al, 2021;Josefsson & Gard, 2012;Sandfort et al, 2013;Zhang et al, 2020 Good/comfortable relationship between HCPs and patients Abramsohn et al, 2013;Carlsson-Lalloo et al, 2016;Lindau et al, 2011;Traumer et al, 2019 Private conversation/private or safe space Abramsohn et al, 2013;Gong et al, 2021;Holmes et al, 2019;Ma et al, 2020 Direct/plain/open discussions Leonardi-Warren et al, 2016;McCallum et al, 2012;Traa et al, 2014 Discussion...…”
Section: Synthesismentioning
confidence: 99%
“…In a cohort study conducted by Wilton et al [18], it was shown that ED was detected 1.45 times more in patients with psoriatic arthritis compared to the normal group. In a similar recent article, it has been shown that psoriasis negatively affects male sexual functions [19]. In their animal experiment, Carneiro et al [20] showed that rats developed endothelial dysfunction and cavernosal smooth muscle hypercontractility after infusion of TNF-α.…”
Section: Discussionmentioning
confidence: 96%
“…In a review, it was emphasized that patients with IBD have more sexual dysfunction and infertility than the normal population, and this was associated with depression and IBD activity [18]. In another review, it was stated that the IIEF score was mostly used in the evaluation of sexual functions in patients with IBD, and the most important risk factors for ED in these patients were depression, disease activity, and history of surgery [19]. In our study, it has been shown that IBD was a risk factor for ED, regardless of the history of surgery and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic inflammatory condition that mainly causes symptoms in gastrointestinal tract such as bloody diarrhea, abdominal pain, fecal urgency, incontinence and weight loss [ 1 ]. Ulcerative colitis (UC) and Crohn’s disease (CD) are representative diseases.…”
Section: Introductionmentioning
confidence: 99%